Fully automated measurements of volumetric breast density adapted for BIRADS 5th edition: a comparison with visual assessment. (September 2021) - Youk, Ji Hyun; Gweon, Hye Mi; Son, Eun Ju; Eun, Na Lae; Kim, Jeong-Ah
Background: Since the 5th edition of BI-RADS was released, prior studies have compared BI-RADS and quantitative fully automated volumetric assessment, but with software packages that were not recalibrated according to the 5th edition. Purpose: To investigate mammographic density assessment of automated volumetric measurements recalibrated according to the BI-RADS 5th edition compared with visual assessment. Material and Methods: A total of 4000 full-field digital mammographic examinations were reviewed by three radiologists for the BI-RADS 5th edition density category by consensus after individual assessments. Volumetric density data obtained using Quantra and Volpara software were collected. The comparison of visual and volumetric density assessments was performed in total and according to the presence of cancer. Results: Among 4000 examinations, 129 were mammograms of breast cancer. Compared to visual assessment, volumetric measurements showed higher category B (40.6% vs. 19.8%) in Quantra, and higher category D (40.4% vs. 14.7%) and lower category A (0.2% vs. 5.0%) in Volpara ( P  < 0.0001). All volumetric data showed a difference according to visually assessed categories and were correlated between the two volumetric measurements ( P  < 0.0001). The group with cancer showed a lower proportion of fatty breast than that without cancer: 17.8% vs. 46.9% for Quantra ( P  < 0.0001) and 9.3% vs. 21.5% for Volpara ( P  = 0.003). Both measurements showed significantly higher mean density data in the group with cancer than without cancer ( P  < 0.005 for all). Conclusion: Automated volumetric measurements adapted for the BI-RADS 5th edition showed different but correlated results with visual assessment and each other. Recalibration of volumetric measurement has not completely reflected the visual assessment.